2020
DOI: 10.1111/exd.14205
|View full text |Cite
|
Sign up to set email alerts
|

SASP‐induced macrophage dysfunction may contribute to accelerated senescent fibroblast accumulation in the dermis

Abstract: The dermis is a tissue rich in collagenous and elastic fibres and supports the epidermal tissue. The network structure of extracellular matrix in the dermis is maintained by molecules such as collagen and elastin produced by fibroblasts. When DNA in fibroblasts is damaged by ageing, UV ray, oxidative stress or other reasons, the production of such fibre molecules is decreased, resulting in dermal dysfunction. DNA damage is able to be sensed and repaired by ATM and ATR kinases and downstream DNA damage response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Ogata et al study how senescent fibroblasts are cleared by macrophages and how their clearance can become suppressed. Using a co‐culture model, authors show a two‐step process, wherein macrophages first induce senescent fibroblast apoptosis via TNFα signalling and then phagocytose dying cells 22 . Intriguingly, the authors also show that the secretome of senescent cells, commonly known as senescence‐associated secretory phenotype (SASP), counteracts their macrophage‐mediated clearance.…”
Section: Fibroblasts and Cellular Senescencementioning
confidence: 98%
See 1 more Smart Citation
“…Ogata et al study how senescent fibroblasts are cleared by macrophages and how their clearance can become suppressed. Using a co‐culture model, authors show a two‐step process, wherein macrophages first induce senescent fibroblast apoptosis via TNFα signalling and then phagocytose dying cells 22 . Intriguingly, the authors also show that the secretome of senescent cells, commonly known as senescence‐associated secretory phenotype (SASP), counteracts their macrophage‐mediated clearance.…”
Section: Fibroblasts and Cellular Senescencementioning
confidence: 98%
“…Fibroblast senescence has been a topic of intense research as it intimately links to tissue‐level ageing and skin pathologies 18–21 . This topic is covered in this issue in a research article 22 and a comprehensive review 23 . Ogata et al study how senescent fibroblasts are cleared by macrophages and how their clearance can become suppressed.…”
Section: Fibroblasts and Cellular Senescencementioning
confidence: 99%
“…For instance, a recently reported co-culture study of senescent dermal fibroblasts and macrophages identified macrophagederived TNFα as an important trigger of senescent cell apoptosis and clearance. 35 Also, the co-culture of dermal fibroblasts and keratinocytes can model particulate matter exposure, where factors released by keratinocytes after heavy metal and hydrocarbon exposure can mediate dermal collagen degradation. 36 In other examples, co-cultures of vitiligo patient-derived CD4 + and CD8 + T cells, 52 or keratinocytes and T cells from psoriasis patients, 37 can be used to advance our understanding of skin disease immunopathogenesis.…”
Section: What Org Anot Ypi C Culture S C An and C An ' T Domentioning
confidence: 99%
“…This is not surprising, considering that humans and rodents are separated by an estimated 96 million years of evolution 21 . Addressing this fact, many studies are being conducted on patient‐derived primary skin cells, including human keratinocytes, 22‐25 melanocytes, 26‐30 fibroblasts 31‐34 and cell co‐cultures 35‐37 . However, typical in vitro culture conditions fail to replicate and, in fact, do not come close to imitating the biomechanical and biochemical complexity of the microenvironment in which cells exist and to which they respond to in native tissues.…”
Section: Bridging the Gap Between “Simplicity” Of In Vitro And Complementioning
confidence: 99%
See 1 more Smart Citation